Paulo Cesar - Carrión G., Paulo Cesar (2016)
The present Project was developed in the city of Loja, due to the need to utilize the resources that exist in the City. Important reason arises the ¨PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A PRODUCTION COMPANY AND DISTRIBUTOR OF SOAPS AND SHAMPOO WITH MEDICINAL PLANTS IN THE CITY OF LOJA, 2013.¨ The study begins with a literature review, where the related conceptual issues Related to the development of this research work. For the realization of the thesis was based, methods and techniques that identified the study population, and see through the implementation of the feasibility survey to be the company, The Market Study was quantified three types of demands; the potential demand of 87% of households Loja consuming SOAPS and 89% shampoo regularly, real demand is made up % of the families Loja who purchase 49 % soap and 47% shampoo currently and effective demand that made up 95% soap anda 83% shampoo of households are willing to buy beet for their normal consuming. The 6 project was determined by applying the offer interviews to one business similar product,. Then developed the technical study is presented where the size of the plant in relation to their capacity and used, defining its macro and micro location and the respective process flow charts for production and marketing. The organizational study found that the company will be legally constituted as a company limited, will have a minimum duration period of 5 years and will name ¨ JABONARTE ¨. The Company will be located in the city of Loja, in the neighborhood EPOCA stret Jamaica between Francia y Hungría Similarly determined hierarchical levels and organizational charts with which the company will begin its work also defined the operating manuals to be clear and defined the functions of the personnel working in the company. The Economic Survey is seen an initial investment of $ 329748 dollars, this investment is divided into fixed assets, deferred and working capital, to the project the financing of investment will be funded with the 34.6% equity and 66.4 % equity financed by the Fiundation Popolorun Progressi The financial evaluation yielded the following results: Net Present value (NPV) of $ 50380,34 the cost benefit ratio it was determined that for every dollar invested will produce a gain of 0.66 cents, the Recovery Period Capital is 4 years, , the 7 internal Rate of Return of the project is 19.3 % and this satisfactory value for the project, sensitivity analysis allowed us to determine that our project supports an increase in costs 17% and a decrease in revenue of11%, giving us to know that the project will not be sensitive to these percentages. With all respects and values quoted above it is concluded that the proposed creation of a producer and marketer of Soap and Shampoo with medicinal plants is feasible and therefore recommended for implementation.